Ceria-modified zeolite: A dual-function approach for effective removal of arsenite from polluted water sources - Suwannatrai, Suttikorn; Tanboonchuy, Visanu; Yan, Dickson Yuk‑Shing; Deewan, Ratthiwa; Khamdahsag, Pummarin (Engineering and Applied Science Research, 2025)
As a carcinogen, arsenic poses a significant threat when it contaminates water sources and agricultural products. In water-based environmental contamination, the most significant arsenic species are arsenate (As(V)) and arsenite (As(III)), with the latter presenting a greater challenge for removal. The development of more efficient adsorbents to successfully remove As(III) from contaminated water is still needed. A novel nanosorbent, ceria supported on Na-P zeolite (CeZ), was created in this study to perform the dual functions of oxidizing As(III) to As(V) and subsequently adsorbing the resulting As(V). CeZ was characterized by XRD, TEM, FTIR, pHpzc, and XANES analyses. Batch adsorption experiments indicated that As(III) removal in the pH range of 3-10 was highly efficient, with a maximum removal capacity of 31.746 mg g-1, which was best explained by pseudo-second-order kinetics. XANES analysis confirmed that CeZ oxidized As(III) to As(V) on the surface during As(III) adsorption. The hydroxyl groups at the CeZ interface play a key role in As(III) sorption, forming inner-sphere monodentate and bidentate complexes. As(III) removal was effective because the sorption reaction was coupled with the oxidation process. Specifically, the CeO2 on the Na-P zeolite surface was the main factor responsible for the oxidation of As(III) to As(V) and its sorption. The As(V) in the solution subsequently adsorbed onto the zeolite.